The Concept of Religion in Current Studies of Scandinavian Pre-Christian Religion - LINDBERG, ANETTE (Temenos - Nordic Journal for the Study of Religion, 2009)
In recent Swedish studies of Scandinavian pre-Christian religion of the late Iron Age, various scholars have questioned the utility of the concept of religion in this field. According to these scholars, the concept of religion obscures the specific character of religions of the small-scale non-literate societies of the pre-Christian Age. In the article, I critically examine suggestions that we abandon the academic concept of religion and replace it with an emic concept, or a concept derived from an emic context. I further argue that this strategy implies an inappropriate dualistic opposition between Scandinavian pre-Christian religion and so-called world religions. I conclude with a critical evaluation of problematic formulations of religious change and variation, presented by the same scholars who criticize the use of the academic category of religion. I try to draw attention to certain problematic implications of these demands. I conclude that we should continue to employ the concept of religion in connection with the religious worlds of pre-Christian societies. The strategy proposed by these scholars may turn out to be merely one more way of imposing misconceptions on this period.